Walking, Body, and The City: Pleasure and The Co-formation of The Self and The City - Islami, Mayarani Nurul (Tuturlogi: Journal of Southeast Asian Communication, 2021)
In Surabaya, as the case of this study, road-based culture has been historically predisposing the way people inhabit the roads. It, then, leads to the ‘acceptance’ of the automobile as the primary mode of mobility. In contrast, there is an emerging youth movement who promotes walking as a way to subvert the current road-based culture and re-invent walking as creative and pleasurable activity as an alternative way of enjoying Surabaya. Through an examination of daily journals, photos, and social media documented by people joining the walking community in Surabaya City, this paper scrutinises the subversive yet creative aspects of walking as an organized activity with a view to generating new insights into the creative potential of walking. In this paper, I argue that the way people experience the world through walking is different to the way people experience the world through automobile travel, and that this generates different versions of, and attachments to, the urban environment of Surabaya.